Inclusive Scenario of Natural Products Obtained From Agar Plant (Aquilaria SP.) In Bangladesh- A Review (Journal of Bio-Science, 2021)
Agarwood is the resinous heartwood obtained from the injured parts of trees under Thymelaeaceae family particularly from Aquilaria species. Agarwood is considered as the most prized non-timber forest product (NTFP) used in attars as well as medicines. Quality of agarwood is the determiner for defining its commercial value. Different countries use different grading system to explain the quality of agarwood. In Bangladesh, more than 45 compounds have been identified so far, mostly sesquiterpenoids, alkanes, fatty acid and other volatile aromatic compounds that are responsible for its fragrance and high prices. Ether extract, total phenolic contents, flavonoid, antioxidant and microbiological tests have shown tremendous positive results. Chemical profiling of agar products is the best identified using GC-MS technique by the various authors. Present review discusses the full scenario of Aquilaria production, inoculation, extraction methods, determination of agarwood quality and chemical constituents of agar oils and possibilities and barriers of this industry in Bangladesh.J. Bio-Sci. 29(2): 151-173, 2021 (December)